Freshwater organic micropollutants alter submerged macrophyte litter decomposition dynamics and microbial community in the surface sediments - Wu, Fan; Yang, Ziyi; Lyu, Tao; Zhou, Xiaohong; Xie, Qingjie (Springer, 2026)
Purpose: Aquatic plant decomposition in aquatic ecosystems is a natural process that releases essential nutrients (C, N and P), which in turn influences the composition and function of sediment microbial communities. Antibiotics, as emerging contaminants widely present in aquatic environment, have the potential to disrupt litter decomposition and microbial activity. However, the ecosystem-level consequences of such alterations remain poorly understood. This study investigated the effects of two model antibiotics, i.e. norfloxacin and doxycycline, present individually and in combination, on nutrient release during the decomposition of Ceratophyllum demersum litter, as well as on sediment physicochemical properties and microbial diversity and community structure. Methods: A controlled microcosm experiment was conducted using C. demersum litter and antibiotic treatments (norfloxacin, doxycycline, and their combination). We monitored nutrient release dynamics (C, N and P) during decomposition, measured sediment physicochemical parameters and characterized sediment microbial diversity and community composition using high‑throughput sequencing. Results: The litter input from C. demersum reduced bacterial diversity in the sediment. Antibiotic exposure, whether single or combined, further slowed nutrient release from decomposing litter and decreased microbial diversity. Moreover, both litter addition and antibiotic exposure significantly altered the composition of the sediment microbial community. Conclusions: The combined inputs of plant litter and antibiotics can jointly reshape microbial community structure and reduce diversity, inhibit nutrient mineralisation and modify the physicochemical characteristics of sediments. This study provides an integrative framework for assessing the potential risks posed by antibiotic contamination and organic matter decomposition to aquatic ecosystem functioning and offers guidance for future ecosystem management.
Keywords: 3007 Forestry Sciences; Environmental Sciences; 30 Agricultural, veterinary and food sciences; 37 Earth sciences; 41 Environmental sciences; Antibiotics; Aquatic ecosystem; Ceratophyllum demersum; Lake restoration; Nature-based solution